DIGITALIZATION AND INSTITUTIONAL REFORM IN THE PUBLIC SECTOR: THE ROLE OF BLOCKCHAIN IN PUBLIC FINANCIAL TRANSPARENCY AND ACCOUNTABILITY - Arwani, Agus; Priyadi, Unggul (Gapenas Publisher, 2025)
This study aims to analyze the role of blockchain technology in improving transparency and accountability of public finances as part of institutional reform in the digital era, against the backdrop of low levels of transparency and high potential for corruption in state budget management. The conceptual approach is carried out through an in-depth literature synthesis that integrates theories of digitalization, blockchain implementation, and institutional reform, highlighting the features of permanent recording, decentralization, and smart contracts in the public financial system. The results of the synthesis show that blockchain can reduce corruption gaps and improve audit mechanisms through real-time data transparency, although its implementation faces technical challenges, non-adaptive regulations, and internal resistance. The conceptual model developed proposes that the success of blockchain adoption is highly dependent on infrastructure readiness, policy adjustments, and organizational culture transformation, thus producing a strategic roadmap for digital reform in the public sector. This study also reveals that obstacles to implementing such technology must be overcome through cross-sector collaboration and progressive policy reforms, which not only improve operational efficiency but also encourage innovation in governance. The results of this study provide a basis for developing a comprehensive digital reform strategy, synergistically integrating technical, policy, and organizational culture aspects, and are expected to inspire innovation in public governance and provide significant theoretical and practical contributions to holistic digital reform.